BALANCING INNOVATION AND PRIVACY: REGULATORY FRAMEWORKS FOR DATA PROTECTION IN INDONESIA’S DIGITAL ECONOMY - Fitriani Rahmadia; Aulia Putri Maulida; Dinda Kurneliasari (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The rapid growth of the digital economy in Indonesia significantly changed the industrial landscape and people’s lives. It makes us realize the importance of regulations to protect personal data, which has encouraged the implementation of stricter personal data protection regulations. Indonesian society does not yet fully understand the importance of personal data protection and the potential risks associated with data misuse. This research uses a normative legal research method, which focuses on the study of laws and regulations, legal doctrines, and other relevant legal sources in the context of personal data protection and the digital economy in Indonesia. This approach will analyze how existing regulations such as Law Number 27 of 2022 concerning Personal Data Protection can create a balance between encouraging innovation and protecting individual privacy in the digital economy. The existence of Law Number 27 of 2022 concerning Personal Data Protection provides a clear legal basis in efforts to maintain consumer privacy in the digital economy era. This law strictly regulates how personal data is collected, used, and processed by third parties. The regulation requires every party that manages personal data to be responsible for the security and use of the data transparently. This also allows room for data-based innovation, but with proper controls, this balance will not only protect society from potential data misuse, but also encourage the development of more ethical and responsible technology.